A case of cutaneous polyarteritis nodosa with elevated serum interleukin-6 levels complicated by leg arterial stenosis and destructive arthropathy of the left ankle. Issue 1 (January 2014) - Horai, Yoshiro; Tokuyama, Ayuko; Sumiyoshi, Remi; Nakashima, Yoshikazu; Suzuki, Takahisa; Okada, Akitomo; Kawashiri, Shin-ya; Ichinose, Kunihiro; Izumi, Yasumori; Miyashita, Taiichiro; Tamai, Mami; Yamasaki, Satoshi; et al.
Abstract: We report a case of a 60-year-old female with cutaneous polyarteritis nodosa (CPN) of the left ankle, accompanied by elevated serum interleukin (IL)-6 levels. Computed tomographic angiography revealed severe narrowing of medium-sized arteries in her left leg. Destructive arthropathy in the left ankle was identified by X-ray and magnetic resonance imaging. This is the first Japanese case of severe CPN complicated by destructive arthropathy. Quantification of serum IL-6 might be useful in diagnosis and evaluation of CPN.